Perkembangan Pendidikan di Era Digital dan Dampaknya Terhadap Psikologi Siswa - Destri Azahra; Ellen Prima (INDO PUBLISHING, 2026)
This article aims to determine the development of education in the digital era and its impact on students’ psychology. The discussion in this article includes the development of digital education, the use of technology in learning, the positive and negative impacts of technology, the influence of social media on students, the challenges faced by teachers and parents, and ways to create healthy learning in the digital era. The method used in this article is a literature study by reviewing various journals, scientific articles, and research results related to digital education and student psychology. The findings show that digital technology has positive impacts on learning, such as easier access to information, increased creativity, and more effective learning for students. However, excessive use of technology can also cause negative impacts, such as social media addiction, decreased learning focus, lack of direct social interaction, and mental health problems among students. In addition, teachers and parents face challenges in supervising the use of technology so that it can be used wisely. Therefore, cooperation between schools, teachers, parents, and students is needed to create healthy and balanced learning in accordance with educational developments in the digital era.